Politics, ethics, teaching and science - Pustovrh, María Carolina (Revista Estomatología, 2019)
The II Congress of ACCBAL and V International Seminar-Workshop of the CICUALES Network entitled: "Politics, Ethics, Teaching and Science", was held from September 19 to 21, 2018 in the city of Santiago de Cali, Colombia. This event was organized jointly by the Universidad del Valle, the Colombian Association for Science and Welfare of Laboratory Animals (ACCBAL), and the Colombian Network of Institutional Committees for the Care and Use of Animals (CICUALES). On this occasion the venue and host was the Universidad del Valle, the heart of research in the southwestern region. The new legislative proposals in animal research aim to obtain great benefits to continue the development and implementation of the principles of the 3Rs (reduction, refinement and replacement).1 In this sense, this event generated interest in political circles and public and private organizations throughout Colombia; it also incorporated the participation of students, researchers, ethics committees and local, regional, national and international directors. It was an important pillar around which conferences and workshops were held, highlighting the need to improve the quality of biomodels and the importance of infrastructure to guarantee the validity, reliability and reproducibility of the research carried out with them.